Sustainability of the water sector in Portugal-an outlook on strategies, dynamics and common practices - Maria Manuela Castro Silva (European Regional Science Association (ERSA), 2005)
To understand the conjunction of human and natural systems and the nature of their interactions has been crucial. The integrated response to the human management of natural systems is nowadays based on "sustainable development” concept which emphasizes the need to make compatible social, economic and environmental systems. But, what does it mean when we consider such a specific resource has it is water, with very essential life-support functions? The design and rhythms of natural and social systems are compatible in a way that they guarantee the supply of this resource, with the quality required for the human needs in the future? To what extend common practices and natural dynamics are forward-looking sustainable water resources development? This paper aims to provide a reflection about these subjects. It mainly addresses issues concerning water from the Portuguese perspective, and highlights the linkages between water resources management and sustainable development. The purposes are to analyse the adequacy of Portuguese water institutions, planning and management to the requirements of the sustainability concept in the context of water resources and also pointing out research needed for improvement of strategies concerning the approach to the problem of water scarcity.
Keywords: 330